Fecal microbiota transplantation - analysis of scientific reports, the role of a nurse - Nowak, Emilia; Widłak, Karolina; Pawłowski, Piotr; Ziętara, Karolina; Orzechowska , Aleksadra; Kościołek, Aneta; Adamska-Kuźmicka, Iwona (Journal of Education, Health and Sport, 2022)
Introduction and objective: Presentation of the subject of fecal microbiota transplantation including the role of a nurse. Review methods: Presentation of the subject of fecal microbiota transplantation including the role of a nurse. Material and methods: A non-systematic review of the literature on the subject of intestinal microflora transplantation was carried out in the available databases: PubMed, Scopus, Web of Science, Google Scholar, EBSCO, ARIANTA. The following keywords were taken into account: microbiota, fecal microbiota transplantation, Clostridium difficile, pseudomembranous enteritis, inflammatory bowel disease. 21 original and review works were qualified: 6 in Polish and 15 in English. An abbreviated description of the state of knowledge: Fecal microbiota transplantation (FMT) involves introducing into the body of a sick recipient a fecal suspension from a healthy donor. The rate of therapeutic success depends on the main disease entity, appropriate selection of the donor of the fecal suspension. The donor should be tested for the presence of numerous pathogens, determining their type and their quality. FMT is recommended when pharmacotherapy ceases to be effective, it is also an adjunctive treatment in the treatment of many dysbiotic diseases. Summary Fecal microbiota transplantation is indicated in severe pseudomembranous enteritis in patients with Clostridium difficile infection. In the experimental phase, there are new indications for the use of FTM, for example, Parkinson's disease, Alzheimer's disease, but it is contraindicated in irritable bowel syndrome. The role of the nurse is limited to preparing the patient, assisting during the procedure, postoperative care, and educating the patient.